Os signos de representação do "eu" e do "outro": A prática da tatuagem carcerária. - Sousa, Adriana Pereira de (2010)
This work is a reflection of the outcome of field research at the Institute Criminal Judge Silvio Porto, João Pessoa - Paraíba State. From interviews and free targeted with the inmates, it was concluded that the intramural prison develops a parallel network of sociability permeated power and submission specifically differentiated from institutionalized power by the state. The practice of tattooing in prisons is within that singular context. Expressing the subjectivity of the individual, the relationship of power and submission, the construction of individual identity and social and social stigma. The practice of tattooing in prisons prepare a universe enigmatic world of crime. A prison tattoo embodies a practical use of cultural and social conflicts delineated by interior and exterior construction of individual identity and social conditions, resulting from these inter-social relations. Therefore this new identity will be built on the edge between faint sudden rupture of self-identity in the world society which he lived and the new identity which is now built upon entry into prison, where the mutilation of the self happens all moment and in all aspects of social life. It is at that threshold where the faint signs that represent crime are entered under the skin. The chosen design and location to be tattooed denounce the particular characteristics of each individual's personality, a ritual identification of the convict as such. A prison tattoo is renowned for its thick strokes and evil designs finished result of the basic techniques used in prisons.